Building User Loyalty Through Excellence Administrative Services in Private Higher Education - Refika, Refika; Latif, Mukhtar; Hakim, Lukman (International Journal of Education, Language, and Social Science, 2024)
This study investigates the quality of administrative services and their impact on the loyalty of educational service users at Islamic colleges in Riau Province. The objectives are: (1) to evaluate the existing quality of administrative services; (2) to assess the level of user loyalty; and (3) to identify aspects of administrative services that can enhance user loyalty. Using a qualitative descriptive-analytical approach, data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman model with data triangulation for validation. The findings reveal that the quality of administrative services at three private Islamic colleges in Riau Province has not successfully increased user loyalty. Contributing factors include a lack of institutional commitment, unresponsive and unfriendly administrative staff, inaccurate data handling, and inadequate service facilities. To improve user loyalty, administrative services must address user needs and expectations by ensuring responsive, accurate, and high-quality service delivery.